2021
DOI: 10.4103/jispcd.jispcd_135_21
|View full text |Cite
|
Sign up to set email alerts
|

The Systematic Review and Meta-analysis of Oral Sensory Challenges in Children and Adolescents with Autism Spectrum Disorder

Abstract: A BSTRACT Objectives: The purpose of the systematic review was to provide a summary and evaluation of oral sensory challenges in children and adolescents with autism spectrum disorder (ASD). Materials and Methods: The review evaluated 19 studies that met the inclusion and search criteria. The review is registered in Prospero Database (CRD42020179852). The 14 studies (8 case–control, 4 cohort, 1 observational, and 1 randomized clinical trial) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…With regards to sensory processing, it is also important at this stage to clarify possible heterogeneity. 'Oral sensory processing’ refers to the processing of food or other objects put in the mouth, and oral sensory sensitivities refer to atypical sensory processing associated with this process (Chaware et al., 2021). Oral sensory sensitivities can encompass atypical processing across multiple sensory domains, including taste, smell and tactile processing, and thus have been synthesised as a distinct sensory domain than taste/smell sensitivities alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to sensory processing, it is also important at this stage to clarify possible heterogeneity. 'Oral sensory processing’ refers to the processing of food or other objects put in the mouth, and oral sensory sensitivities refer to atypical sensory processing associated with this process (Chaware et al., 2021). Oral sensory sensitivities can encompass atypical processing across multiple sensory domains, including taste, smell and tactile processing, and thus have been synthesised as a distinct sensory domain than taste/smell sensitivities alone.…”
Section: Resultsmentioning
confidence: 99%
“…While oral sensory processing was associated with mealtime behaviours, food repertoire and food neophobia, it should be noted that oral processing encompasses multiple sensory domains, including taste/smell and tactile sensitivities (Chaware et al., 2021). The current review found evidence to suggest that tactile sensitivities may not play as significant a role, with studies either reporting non‐significant associations (Nadon et al., 2011; Zickgraf & Mayes, 2018) or having measurement limitations that prevent generalisable or comparable conclusions (e.g., Suarez et al., 2012, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The work concentrated on analysing psychiatric disorders and collected studies from the past 10 years that employ speech to identify the presence or severity of mental disorders. In 2021, another review was published to summarise and evaluate oral sensory problems in children and adolescents with ASD [ 18 ]. A systematic search was reported in the work with the published articles from January 2000 to December 2018, concentrating entirely on ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is a significant need for oral stimulation targeting the articulating surface of the speech element, increasing muscle coordination, gratifying sensory demands, or lessening sensory overload, which may control feeding and eating behavior. 12 Hence, oro-motor sensory stimulation may assist in the advancement of both speech and feeding issues in ASD children. Therefore, the current organized stepwise graded module was developed to benefit therapists in assessing, setting goals, and identifying activities to support feeding problems in children with ASD.…”
Section: Discussionmentioning
confidence: 99%